Evidence against immune haemolysis in falciparum malaria in Thailand. - Merry, A; Looareesuwan, S; Phillips, R; Chanthavanich, P; Supanaranond, W; Warrell, D; Weatherall, D (1986)
Evidence of immune mediated haemolysis was sought in 83 patients with P. falciparum malaria in eastern Thailand. Amongst 73 patients with uncomplicated infection 12 (16.4%) had a weakly positive direct antiglobulin test (DAT). The incidence in 32 children aged 8-16 years was similar to that in adults. Of 10 patients with cerebral malaria, six adults, all of whom were in unrousable coma, had a positive DAT. Erythrocyte-bound IgG1 accounted for the positive DAT in all cases; sensitization with complement or other IgG subclasses was not found. Patients with uncomplicated malaria had a median value of 70 IgG molecules per erythrocyte compared with 65 molecules per cell in 67 healthy controls. This difference was not statistically significant but could account for the lower incidence of a positive DAT in control subjects (4.5%). There was no correlation between the number of IgG molecules per cell and the degree of anaemia during the acute or convalescent phases of the infection. There is no evidence from this study that an immunohaemolytic process contributes to the anaemia of falciparum malaria in eastern Thailand.